Examining Critical Factors of Contact Tracing Apps in the Context of COVID-19 - Geis, Thomas (My University, 2021)
The current COVID-19 pandemic influences citizens in several aspects of their lives. In order to inhibit the spreading of the virus, governments utilize several methods and tools, including shutdown, social distancing procedures, and contact tracing apps. These apps should notify and warn smartphone users if they have had any recent encounters with individuals that tested positive for COVID-19. However, many citizens raise concerns and refuse to use them. As research about contact tracing apps and their adoption is scarce, this thesis aims to identify factors that are critical to a person’s readiness to accept these apps and to disclose personal data on them, especially in the context of the Coronavirus. First, previous literature about such factors in similar services, for example online sites and social networks, has been identified and summarized via a structured literature review. Based on this literature, a research framework has been created and explained. In order to identify relevant factors for an individual’s data disclosure intention on COVID-19 tracing apps, 21 subjects have been questioned via semi-structured interviews about their attitudes toward the German variant “Corona Warn App” (CWA). The results were then presented and discussed by comparing them to the research framework. Overall, three main findings emerge: (1) The privacy calculus is less relevant for the CWA than it is for other contexts. (2) The construct of user value can be observed in both contexts but is represented differently. While utilitarianism and hedonism are the primary drivers of value in the research framework, egoism and altruism are reported to be the main factors that generate value in the context of the CWA. (3) The constructs of knowledge, anonymity, activity, location, ease of use, age, and social circle have been considered as critical factors within the Coronavirus tracing context but were not covered within the research framework. This thesis contributes to current research by proposing relevant factors for an individual’s intention to disclose personal data on Coronavirus tracing apps. Therefore, there should be further research on how significant these factors truly are.
Keywords: adoption, contact tracing, Corona Warn App, COVID-19, critical factors, online services, pandemic, privacy